Digital Strategies in the Food Service Industry: an Analysis of the Influence of Online Services, Serving Speed, and Packaging Quality on Customer Satisfaction - Putri Pujiningtyas; Yossie Rossanty; Firman Ario (International Journal of Economics and Management, 2026)
This study aims to analyze the influence of online service, serving speed, and food packaging quality on customer satisfaction at Ayam Bakar Penyet Palapa Gaperta. This study uses a quantitative approach with a survey method by distributing a Likert-scale questionnaire to customers who have placed at least two online orders within the last three months. The data analysis techniques used included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-tests), simultaneous tests (F-tests), and the coefficient of determination (R²) using SPSS software. The results of the study indicate that online service, serving speed, and food packaging quality have a positive and significant influence on customer satisfaction, both partially and simultaneously. Responsive online service, a fast and timely serving process, and packaging quality capable of maintaining food safety and quality have been proven to enhance customer satisfaction. The limitations of this study lie in the relatively small number of respondents, the research focus being limited to a single culinary SME in Medan, and the use of a  quantitative approach without the support of in-depth interviews.  This study is expected to contribute to the development of digital service marketing management, particularly in the field of digital culinary service strategies, and to serve as a basis for evaluation and recommendations for culinary SME operators in improving service quality  and customer satisfaction.